Pengaruh Latihan Motor Skill Terhadap Peningkatan Fungsi Kognitif Pada Anak Kelas 1 SD Alfirdaus Surakarta - ROCHMAH, YUNITA NUR; , Dwi Rosella K, S.St FT., M.Fis (2017)
BACKGROUND: The current phenomenon in children decreased physical fitness and pressure of school to improve cognitive performance. Motor skill exercise that consists of obstacle course and walking on the balance beam is one method of exercise selected in terms of improvement of cognitive function. PURPOSE: To know the effect of motor skill exercise on cognitive function in children 1'st grade at Alfirdaus elementary school Surakarta. SUBJECTS: all students at alfirdaus elementary school who have Stroop test scored over 45 seconds, the subject of as many as 40 children from 6 until 7 years old and got the inclusion criteria were divided into 2 groups. Group I got the treatment with the frequency of exercise three times a week and the second group got the treatment with frequency of exercise 1 time a week. RESEARCH DESIGN: Pretest and posttest With Control Group Design, tested for normality with Shapiro Wilk, tested the effect with the paired samples t-test, and different effect test with the independent sample t-test, treatment for 1 month. RESULTS: Normality test cognitive function before treatment in group I (p > 0,05) word card value of p = 0,89, colour card value of p = 0,176 dan word and colour card value of p = 0,17. After treatment word card value of p = 0,85, colour card value of p = 0,42 dan word and colour card value of p = 0,6. Group II before treatment word card value of p = 0,24, colour card value of p = 0,06 dan word and colour card value of p = 0,160. After treatment word card value of p = 0,24, colour card value of p = 0,150 dan word and colour card value of p = 0,180.. Tested the effect in Group I of word cards, color cards, the word and color card value of p = 0.000 (p <0.05). Group II (p <0.05) word card value of p = 0.000, color card 0.001, the word and color card value of p = 0.001. The influence of different test group I and group II word cards, color card, the word and color card value of p = 0.000 (p <0.05). From the descriptive data show that there are differences in cognitive function before and after treatment in each group and there are differences in cognitive function before and after treatment between groups I and II. CONCLUSION: There is an influences and difference between the motor skill exercise to increase cognitive function between test group I and II.